Microstructure and photoluminescence of Eu-doped Sr3Al2O6 phosphors calcined with and without H3BO3 flux. Issue 22 (15th November 2022) - Hong, Ji Ho; Lee, Ja Yeon; Kang, Ji Ho; Lee, Joon Yup; Jang, Ho Seong; Cho, Seong-Yong; Kim, Dong Hun
Abstract: The development of highly efficient and stable red phosphors fabricated using cost-effective and simple mass-production methods is essential for applications in future displays and lighting devices. Herein, we investigate the phase formation, microstructures, and luminescence properties of Sr3 Al2 O6 :Eu powders synthesized using a solid-state reaction process. Single-phase Sr3 Al2 O6 :Eu phosphors exhibiting excellent photoluminescence with color-tunable orange-red and red colors under different excitation wavelengths were successfully synthesized. The optimal Eu doping concentration of Sr3 Al2 O6, yielding strong photoluminescence with phase stability, was 5 at. %, with the concentration quenching point determined by systematic exploration. The addition of H3 BO3 as a flux significantly affected the grain size and improved the emission intensity of the synthesized (Sr0.95 Eu0.05 )3 Al2 O6 phosphors up to 12.5 wt %, while secondary phases were formed at higher flux concentrations. The photoluminescence intensities of the 5 D0 → 7 F1 and 5 D0 → 7 F2 transitions of 12.5 wt % H3 BO3 added (Sr0.95 Eu0.05 )3 Al2 O6 increased by 3.4 and 4.2 times compared with the flux-free powders under the 394 nm-wavelength excitation, while the decay time decreased from 7.35 to 5.40 ms. Our report of the enhanced photoluminescence intensity and shortened decay time of (Sr0.95 Eu0.05 )3 Al2 O6 phosphors following the flux addition is promising for production of single-phase phosphors emitting multi-colors, which is needed for optical devices activated by various excitation frequencies.